The effect of problem-based learning and naturalist intelligence on students' understanding of environmental conservation - S. Suhirman; Y. Yusuf (JPBI (Jurnal Pendidikan Biologi Indonesia), 2019)
Environmental conservation understanding is one of the crucial factors which determines student attitudes and behavior towards the environment. This study aimed to investigate the effects of problem-based learning and naturalist intelligence on the students' understanding of environmental conservation. This experimental research was conducted at Madrasah Aliyah Negeri (MAN) 1 Praya which employed factorial design. The first factor was the levels of naturalist intelligence (high and low) and the second factor was learning forms (problem-based and expository learning). Two groups were randomly selected from X-MIPA graders of MAN 1 Praya. The data were collected through tests which then were analyzed using ANOVA at 0.05 significance level. The results of the study indicated that problem-based learning affected the students’ understanding of environmental conservation, while naturalist intelligence did not affect it. Furthermore, there were no interaction between these two factors.